Formulation of Micellar Based Water from Piper crocatum Leaves Extract Using Various Concentrations of Poloxamer 188: Formulasi Micellar Berbasis Air Ekstrak Daun Sirih Merah (Piper crocatum) dengan Variasi Konsentrasi Poloxamer 188 - Pratiwi, Hani; Okzelia, Sari Defi; Afiah, Mawar (Jurnal Farmasi Galenika (Galenika Journal of Pharmacy) (e-Journal), 2024)
Background: Micellar based water (micellar water) is a preparation used to clean the face or makeup with water-based ingredients. Micellar water has moisturizing additives accompanied by antioxidants. Piper crocatum leaves is one of the plants that contain flavonoid compounds so it has the potential as an antioxidant. Micelles are the main component in micellar water preparations derived from amphiphilic block copolymer-type surfactants such as poloxamer. Objectives: The purpose of this study was to formulate, evaluate, and observe the antioxidant activity of the most optimum formulation of micellar based water preparations of Piper crocatum leaves extract with variations in poloxamer 188 concentrations. Material and Methods: The stages of this research were material preparation, extract characteristics evaluation, production of micellar preparations at poloxamer 188 concentrations of 1% (F1); 1.5% (F2); and 2% (F3); preparation characteristics evaluation, stability, particle size, antioxidant activity assay for the optimum formula, and irritation test. Results: The results of the evaluation showed that the pH of the preparation ranged from 4.54 - 4.76; viscosity values ranged from 16.40 - 24.26 cP; particle size ranged from 170.6 – 349.9 nm; and the entire formula did not irritate the skin. Conclusions: Based on the results of this study, it was found that the most optimal concentration of poloxamer 188 was 2% (F3) with IC50 value of 119.63 ppm which categorized as a moderate antioxidant activity.